2001
DOI: 10.1001/archpedi.155.10.1131
|View full text |Cite
|
Sign up to set email alerts
|

Empowering Children and Families With Information Technology

Abstract: Patient empowerment is the enhanced ability of patients to actively understand and influence their health status. Information is the key to patient empowerment. Without information, children and families cannot engage in meaningful discussions or make thoughtful decisions regarding medical care. Information sharing is a model for patient interaction with the health care system that may significantly improve the care of children and families. This article focuses on information technologies that utilize user-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(52 citation statements)
references
References 36 publications
0
51
0
1
Order By: Relevance
“…Current research has shown that the adoption of new technologies that allow for patient transactions outside the primary care office can significantly affect the effectiveness, patient-centeredness, timeliness, and efficiency of child development and health promotion practice. [6][7][8][9][10] The potential benefits of this type of technology for WCC are considerable. If developmental and psychosocial screening can be accomplished through non-face-to-face transactions over the Internet and communicated to the PCP before the visit, the PCP can ensure that the specific needs of the family are met during the WCC visit in an efficient and effective manner.…”
Section: Introductionmentioning
confidence: 99%
“…Current research has shown that the adoption of new technologies that allow for patient transactions outside the primary care office can significantly affect the effectiveness, patient-centeredness, timeliness, and efficiency of child development and health promotion practice. [6][7][8][9][10] The potential benefits of this type of technology for WCC are considerable. If developmental and psychosocial screening can be accomplished through non-face-to-face transactions over the Internet and communicated to the PCP before the visit, the PCP can ensure that the specific needs of the family are met during the WCC visit in an efficient and effective manner.…”
Section: Introductionmentioning
confidence: 99%
“…In plaats van het internet te diskwalificeren als informatiebron (zie Drayton et al, 2014) worden in studies over de kwaliteit van informatie op het internet vaak vier opties onderscheiden om de risico's van gebrekkige informatie tegen te gaan: het vergroten van de 'mediawijsheid' van de gebruiker (Bernhardt & Felter, 2004;Boston, Ruwe, Duggins, & Willging, 2005;Chen et al, 2000;Semere et al, 2003), het versterken van de verantwoordelijkheid van de beroepskrachten (D'Alessandro & Dosa, 2001;Nieuwboer, 2014;Sim et al, 2007), het hanteren van een 'gouden standaard ' (D'Alessandro & Kingsley, 2002;Hardwick & MacKenzie, 2003;Scullard, Peacock, & Davies, 2010) en het instellen van een keurmerk (Dornan & Oermann, 2006;HON).…”
Section: Discussieunclassified
“…At the forefront of these changes is the patient who has become increasingly empowered and is now demanding greater access to their healthcare data and involvement in decision-making [1][2][3]. While radiology practice has traditionally limited communication of medical imaging report data between radiologists and referring clinicians, increasing emphasis is being placed on direct radiologistpatient communication, which has been mandated in breast imaging with the passage of the Mammography Quality Standards Act (MQSA) [4].…”
Section: Introductionmentioning
confidence: 99%